Discovery of Novel Tyrosine Ammonia Lyases for the Enzymatic Synthesis of p‐Coumaric Acid. (7th April 2022) - Brack, Yannik; Sun, Chenghai; Yi, Dong; Bornscheuer, Uwe T.
Abstract: p ‐Coumaric acid ( p ‐CA) is a key precursor for the biosynthesis of flavonoids. Tyrosine ammonia lyases (TALs) specifically catalyze the synthesis of p ‐CA from l ‐tyrosine, which is a convenient enzymatic pathway. To explore novel and highly active TALs, a phylogenetic tree‐building approach was conducted including 875 putative TALs and 46 putative phenylalanine/tyrosine ammonia lyases (PTALs). Among them, 5 TALs and 3 PTALs were successfully characterized and found to exhibit the proposed enzymatic activity. The TAL from Chryseobacterium luteum sp. nov (TAL clu ) has the highest affinity ( K m =0.019 mm ) and conversion efficiency ( k cat / K m= 1631 s −1  ⋅ mm −1 ) towards l ‐tyrosine. The reaction conditions for two purified enzymes and their E. coli recombinant cells were optimized and p ‐CA yields of 2.03 g/L after 8 hours by TAL clu and 2.35 g/L after 24 h by TAL from Rivularia sp. PCC 7116 (TAL rpc ) in whole cells were achieved. These TALs are thus candidates for the construction of whole‐cell systems to produce the flavonoid precursor p ‐CA. Abstract : Using a phylogenetic tree‐building approach, five novel tyrosine ammonia lyases (TALs) and three novel phenylalanine/tyrosine ammonia lyases (PTALs) were identified. The enzymes were biochemically characterized and the optimal conditions for a whole cell E. coli biotransformation were determined. Under these conditions p ‐coumaric acid ( p ‐CA) yields of 2.03 g/L after 8 hours by TAL clu and 2.35 g/L after 24 hours by TAL rpc could be achieved.